COMBINED RESISTIVITY AND ELECTROMAGNETIC INVESTIGATIONS FOR GROUNDWATER IN THE PRECAMBRIAN AREA OF SEMI-ARID PARAÍBA - Schuster, Hans Dieter; Vitorino Filho, Sebastião; Bischoff, Jürgen Heinrich (Águas Subterrâneas, 1988)
Resumo não disponível.